A journey to the center of the earth - Verne, Jules, 1828-1905 ([Boston, Mass] : Thomson Heinle, 2005)
This is the story of Professor Lidenbrock, his nephew Axel and their quest for the secrets contained at the earth's core. Led by Hans, their Icelandic guide, they descend deeper into the planet than anyone has ever gone before
Title from container
Keywords: Explorers -- Fiction; Science fiction